Proteínas de exocitose do GLUT4 e suas interações em resposta à insulina nos tecidos muscular esquelético e adiposo de animais submetidos à desnutrição proteica na vida intrauterina e recuperados - Cunha, Clarissa Felfili da (2013)
Introduction: Changes in maternal nutrition during critical periods of fetal development and lactation can lead to alterations in the offspring insulin sensitivity. Glucose uptake by GLUT4 in muscle and white adipose tissue is mediated by the SNARE complex, composed by the tSNARE, Syn4 and SNAP23, and the v-SNARE, VAMP-2, which is regulated by additional proteins, such as Munc18c. Through a non-classical pathway, involving Munc18c as an IR substrate, insulin signals to the SNARE complex. Objective: Therefore, we evaluated phosphorylation and association events of SNARE machinery of GLUT4 in skeletal muscle and white adipose tissue insulin stimulated. Methods: Adult rats were fed a diet of 17% protein (C group) or 6% protein (LP group) during fetal life, suckling and after weaning, and rats receiving 6% protein during fetal life and suckling followed by a 17% protein diet after weaning (R group) up to 90 days of life. An intraperitoneal ITT was performed to evaluate the insulin sensibility through glucose disappearance rate (Kitt). Skeletal muscle and adipose tissue fractions were used to determine the total protein content of IR, GLUT4, SNARE proteins and Munc18c, as well as association and phosphorylation assays. Results: LP rats showed the highest insulin sensitivity as well as adipose protein content of GLUT4, Syn4, VAMP-2 and IR and its phosphorylation. A lower Munc18c phosphorylation in LP rats resulted in an increased association with Syn4 in adipose tissue. In R rats, these variables were similar to those of C, and an increased Munc18c phosphorylation resulted in a decreased association with Syn4 compared to LP rats. Conclusion: These results suggest that the increased insulin sensitivity of LP may result of tissue specific alterations in non-classical insulin pathway, as well as increased SNARE proteins content.